The Effect of Tiki-Taka Game-Based Training on Passing Accuracy Improvement among Under-13 Football Players - Azza Mulhaq; Zikrur Rahmat; Mahmudin Aritanoga (Winaya Inspirasi Nusantara Foundation, 2026)
Passing accuracy underpins effective tactical execution in youth football, yet young players frequently struggle with spatial consistency during competitive match play. This study evaluated how a Tiki-Taka game-based training regimen affects passing accuracy in Under-13 (U13) players at SSB PSAN Neusu Banda Aceh. Utilizing a quantitative pretest–post-test control group design, we allocated 30 U13 athletes into either an experimental group (n = 15) that underwent Tiki-Taka training or a control group (n = 15) that followed a conventional training curriculum. We assessed passing proficiency via the Soccer Passing Accuracy Test before and after the intervention. Statistical analysis comprised descriptive metrics, Shapiro-Wilk normality verifications, Levene’s homogeneity checks, Wilcoxon Signed Rank Tests, and Independent Samples t-tests. The experimental cohort demonstrated significant post-intervention gains, with mean passing accuracy scores climbing from 4.73 to 6.20 (p = .001). Conversely, the control group showed no meaningful improvement (p = .180). Post-test comparisons revealed a stark performance divergence between the two cohorts (p = .001), establishing that Tiki-Taka game-based intervention outperforms standard drills. Integrating high-density, short-passing games into youth academies enhances immediate technical execution. It also nurtures spatial awareness and rapid collaborative processing, offering coaches a structured framework to optimize tactical development.